2019
DOI: 10.3390/rs11070756
|View full text |Cite
|
Sign up to set email alerts
|

Semi-Automatic Oil Spill Detection on X-Band Marine Radar Images Using Texture Analysis, Machine Learning, and Adaptive Thresholding

Abstract: Oil spills bring great damage to the environment and, in particular, to coastal ecosystems. The ability of identifying them accurately is important to prompt oil spill response. We propose a semi-automatic oil spill detection method, where texture analysis, machine learning, and adaptive thresholding are used to process X-band marine radar images. Coordinate transformation and noise reduction are first applied to the sampled radar images, coarse measurements of oil spills are then subjected to texture analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…The classification-accuracy assessment using these three 2-by-2 matrix domains (diagonal, horizontal, and vertical) differs from other published investigations exploring oil-slick LDA classifiers, which do not report their accuracies in such a succinct manner as we do here. Some papers ignore the vertical-analysis metrics (e.g., [35]) or even both, horizontal and vertical (e.g., [34,36]).…”
Section: Classification-accuracy Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The classification-accuracy assessment using these three 2-by-2 matrix domains (diagonal, horizontal, and vertical) differs from other published investigations exploring oil-slick LDA classifiers, which do not report their accuracies in such a succinct manner as we do here. Some papers ignore the vertical-analysis metrics (e.g., [35]) or even both, horizontal and vertical (e.g., [34,36]).…”
Section: Classification-accuracy Assessmentmentioning
confidence: 99%
“…These authors confirmed that LDAs were effective with 81% to 87% success rates depending on the choice of accuracy metric; but three other methods were more effective. In an attempt to use LDAs, among three other techniques for detecting oil spills, Liu et al [36] explored three different marine radar images to build a semi-automatic adaptive thresholding detection method. Their LDAs were capable of flagging about 80% of the spills visually identified by human interpretation, with LDAs being the second-best technique.…”
Section: Introductionmentioning
confidence: 99%
“…Several works [33] investigate the use of the capabilities of Convolutional Neural Networks (CNNs) in many steps of the classical detection process that outperform conventional approaches. For example, a text classifier based on a neural network algorithm is used for the detection of dark features by [21]. The work of [14] employs a stacked auto-encoder (SAE), and use a Deep Belief Network (DBN) to optimize the polarimetric feature sets.…”
Section: Relative Work To the Oil Slick Detectionmentioning
confidence: 99%
“…However, due to the confidentiality policy of commercial companies, the core technologies have not yet been published. Since 2010, based on the shipboard radar images collected in the oil spill accident of Dalian on July 16, 2010, the researchers of Dalian Maritime University have successively published the achievements of oil spill monitoring by using adaptive threshold methods, active contour models, and machine learning methods [16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%